Analysis of single nucleotide polymorphisms associated with the vitamin D pathway in the placentas of women with gestational diabetes mellitus: a laboratory study - Mi Ju Kim; Hyun Mi Kim; Hyun-Hwa Cha; Won Joon Seong (Journal of Yeungnam Medical Science, 2023)
Background The aim of this study was to analyze the single nucleotide polymorphisms (SNPs) of genes known to be involved in vitamin D metabolism in the placenta using the placental tissue of mothers diagnosed with gestational diabetes mellitus (GDM) to determine whether the SNPs and occurrence of GDM are related. Methods We enrolled 80 women of the same gestational age, 40 with and 40 without GDM. The placenta was obtained from each woman after delivery and SNP genotyping was performed on seven SNPs in the CYP27B1 (rs10877012), CYP24A1 (rs2248359, rs6013897, and rs2209314), and GC (rs2282679, rs16847024, and rs3733359) genes. Maternal serum 25-hydroxyvitamin D levels were measured during the first trimester of pregnancy and before delivery. Results At the time of delivery, vitamin D levels were lower (21.05±12.05 mg/dL vs. 31.31±20.72 mg/dL, p=0.012) and the frequency of vitamin D deficiency was higher (60.7% vs. 32.5%, p=0.040) in the GDM group. In women with GDM, the G allele of rs10877012 was more common (86.3% vs. 65.0%, p=0.002). The rs10877012 GG genotype was more common in the GDM group (72.5% vs. 42.5%, p=0.007) and the rs10877012 TT genotype was more common in the control group (12.5% vs. 0%, p=0.007). Conclusion Mothers with GDM have lower serum concentrations of vitamin D before delivery than healthy controls and vitamin D deficiency is common. A polymorphism in CYP27B1 (rs10877012), is considered to be a cause of GDM pathogenesis.